The Challenges for Anti-Racist Pedagogies from a Geo-biopolitical Perspective - Carril, Lourdes de Fátima Bezerra (ODEERE, 2023)
This work aims analyze the implementation of the Art. 26-A (Law 11.645/08), in the Brazilian public school, seeking to contribute with the debates on the challenges that prevent the presence or absence of African, Afro-Brazilian culture and indigenous, in school curricula. We analyze that thoughts are transformed into practices of governmentality for which the geopolitics associates to the biopower, catalyzing social control strategies. In this matter we use the concept of coloniality of power to discuss the identities demands and articulations, and how the structural racism transits in their various dimensions. Thus, the methodological path is going by analyses of articles about the theme, taking the publications from the 2023 year, when the legislation turns 20 years old. The reading leads to the racial thinking of some intellectuals about Brazilian social formation, concluding that a pedagogical practice of social and cultural homogeneity is maintained in the school space. In it, the myth of racial democracy is still in force as a historical-cultural perspective after the abolition of slavery, thus engendering long-lasting geopolitics, denying identities in school daily life, and preserving the social order.